“Dead Hand Goods” in a legal-historical perspective - Pietrzak, Helena (Prawo Kanoniczne, 2024)
In past centuries, the Roman Catholic Church collected movable and immovable property, easements and privileges. Like every entity, it needed specific goods to achieve its goals (the mission of the Church). History shows that both expropriation of owned property and restitution also affected the Church. Similarly, in the post-war period, as a result of changes in the State-Church relationship, an inevitable conflict began in Poland, which consequently turned into a "propaganda war" waged by the state authorities against the Church. Its scope covered many areas of life, both religious and financial The communist authorities tried hard to deprive the Church of many institutions and reduce its assets. The "goods of the dead hand" have become a tool for limiting the material base of the Church, and thus the possibility of financing activities that go beyond the framework of strictly cult activities. Strict control of the Church's property and its institutions, including administrative repressions and propaganda campaigns, were to lead to the Church's subordination to the authorities, weakening its authority in society, and even to its complete liquidation.